2014
DOI: 10.3109/10409238.2014.953626
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in ABC transporters: Type I, II and III importers

Abstract: ATP-binding cassette transporters are multi-subunit membrane pumps that transport substrates across membranes. While significant in the transport process, transporter architecture exhibits a range of diversity that we are only beginning to recognize. This divergence may provide insight into the mechanisms of substrate transport and homeostasis. Until recently, ABC importers have been classified into two types, but with the emergence of energy-coupling factor (ECF) transporters there are potentially three types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 100 publications
2
111
0
Order By: Relevance
“…ABC importers are further divided into three categories; Type I, Type II and Type III transporters (also known as energy-coupling factor (ECF) transporters) [5]. This distinction evolved out of the differences in overall architecture and variations in the transport mechanism of each subtype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABC importers are further divided into three categories; Type I, Type II and Type III transporters (also known as energy-coupling factor (ECF) transporters) [5]. This distinction evolved out of the differences in overall architecture and variations in the transport mechanism of each subtype.…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies of ABC transporters in complex with SBPs have revealed how each SBP forms a complex with the TMDs of its cognate transporter to deliver substrate to the translocation pathway. Binding of substrate by the SBP and formation of the transporter complex determines selectivity for substrate transport (for comprehensive reviews on the mechanism and selectivity of ABC transporters see [5,1113]). Alternatively, the S component of the ECF transporter binds substrate and rearranges position to deliver it across the lipid bilayer [14].…”
Section: Introductionmentioning
confidence: 99%
“…BCCT carriers are membrane proteins, most of which contain 12 predicted transmembrane ␣-helices (14,15). ABC transporters are one of the oldest and largest protein superfamilies and are ubiquitous from prokaryotes to eukaryotes (16)(17)(18). In bacteria, ABC transporters are primarily responsible for cellular uptake of nutrients and the export of harmful substances (19).…”
mentioning
confidence: 99%
“…Indeed, the structural basis of binding protein interactions has recently been demonstrated for the ECF (energy-coupling factor) transporters, a distant branch of ABC importers with multiple binding protein partners per transporter (77). These studies may provide the framework for understanding the specificity of protein interactions in type I and type II ABC importers and provide additional insight into the diverse means by which ATP is utilized for transport (78). In conclusion, we propose that, as additional ABC importers are characterized, a spectrum of traits rather than discrete combinations will be the hallmark of this protein superfamily.…”
Section: Discussionmentioning
confidence: 99%